Finding the Sweet Spot between Ethics and Aesthetics: A Social Entrepreneurial Perspective to Sustainable Fashion Brand (Juxta)Positioning. Issue 5 (19th October 2020) - Bandyopadhyay, Chinmoy; Ray, Subhasis
Abstract: Eco-fashion brands strive to strike a balance between sustainability and product-related aspects. While much has been written on the branding of sustainable fashion, little is known about the positioning strategies that have both sustainability and fashion appeal. This study aims to fill the gap, guided by the research question: how sustainability and product functionality-related aspects are dealt with while positioning a fashion brand? Using an illustrative case study of an Indian social enterprise, Upasana, we explore how fashion brands identify and work on a positioning strategy that balances the fashion and sustainability-related aspects of their products. Our paper is based on multiple site visits over the last seven years, email communications, direct observations, analysis of the company website, brochures, and in-depth interviews with the founder. Our findings suggest three aspects that should be highlighted in the positioning of a sustainable fashion brand: (i) authenticity of the products and business processes (ii) local and/or traditional aspects of the product including its design (iii) an appealing backstory with market relevance. By uncovering the brand positioning strategies adopted by a social enterprise, this article contributes to our understanding of how sustainable fashion brands can create a favorable image among the stakeholders.